Attenuation of the extracellular matrix restores microglial activity during the early stage of amyloidosis. Issue 1 (31st August 2020) - Stoyanov, Stoyan; Sun, Weilun; Düsedau, Henning Peter; Cangalaya, Carla; Choi, Ilseob; Mirzapourdelavar, Hadi; Baidoe‐Ansah, David; Kaushik, Rahul; Neumann, Jens; Dunay, Ildiko Rita; Dityatev, Alexander
Abstract: In the advanced stages of Alzheimer's disease (AD), microglia are transformed to an activated phenotype with thickened and retracted processes, migrate to the site of amyloid‐beta (Aβ) plaques, and proliferate. In the early stages of AD, it is still poorly understood whether the microglial function is altered and which factors may regulate these changes. Here, we focused on studying microglia in the retrosplenial cortex (RSC) in 3‐ to 4‐month‐old 5xFAD mice as a transgenic mouse model of AD. At this age, there are neither Aβ plaques, nor activation of microglia, nor dysregulation in the expression of genes encoding major extracellular matrix (ECM) molecules or extracellular proteases in the RSC. Still, histochemical evaluation of the fine structure of neural ECM revealed increased levels of Wisteria floribunda agglutinin labeling in holes of perineuronal nets and changes in the perimeter of ECM barriers around the holes in 5xFAD mice. Two‐photon vital microscopy demonstrated normal morphology and resting motility of microglia but strongly diminished number of microglial cells that migrated to the photolesion site in 5xFAD mice. Enzymatic digestion of ECM by chondroitinase ABC (ChABC) ameliorated this defect. Accordingly, the characterization of cell surface markers by flow cytometry demonstrated altered expression of microglial CD45. Moreover, ChABC treatment reduced the invasion of myeloid‐derived mononuclear cells into the RSC of 5xFAD mice. Hence, the migration of both microglia and myeloid cells is altered during the early stages of amyloidosis and can be restored at least partially by the attenuation of the ECM. Main Points: The structure of neural ECM, expression of microglial CD45 and migration of microglial cells to the lesion sites are changed at the early stage of amyloidosis in 5xFAD mice. Migration is rescued by enzymatic digestion of ECM with chondroitinase ABC.